Investigation of Risk Factors for Tunneled Hemodialysis Catheter Dysfunction - Khaliq Ur Rehman, Rizwan Aziz Qazi, Khalid Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Tunneled central venous catheters (CVC) is a flexible tube with prolonged vascular access providing for the management of intravenous medication treatments, fluids, or total parenteral nutrition, repeated blood sampling, and hemodialysis (HD). Objectives: The main objective of the study is to investigate the risk factors for tunneled hemodialysis catheter dysfunction. Material and methods: This observational study was conducted in Akbar Niazi Teaching Hospital, Barakahu, Islamabad during June 2022 till October 2022. All patients who underwent central venous catheterization for the first time in the hospital were included in the study. All catheterizations were performed ultrasound-guided and rechecked by fluoroscopy to confirm the proper replacement of the catheter in the Cava-atrial junction. Results: The data was collected from 235 patients. One hundred sixty-three patients (72.4%) had no CVC malfunction and sixty-two (27.6%) patients had malfunction. The median duration of follow-up was 162 days for patients with no malfunction and 48.5 days for patients with CVC malfunction. Practical implication: We can easily find the catheter related complications after reading this research analysis. Conclusion: It is concluded that the placement of TDCs in patients should be considered the last resort; however, with the increased use of TDCs and experience, the number of catheter-related complications can be expected to decrease. Keywords: TDCs, Catheter, CVC, Malfunction, Complications